Impact of Occupational Hazards on the Technical Efficiencies of Oil Palm Processors in Edo State, Nigeria - Oyekale, Tolulope Olayemi; Ugbekile, Peace Chukwuyem; Adekunle, Chioma Patricia; Oluwalana, Elizabeth Olufunmilayo; Sam-Wobo, Sammy Olufemi (International Journal of Environment, Agriculture and Biotechnology, 2022)
This study examined the effect of occupational hazards on the technical efficiencies of oil palm processors in Edo State. A multistage sampling procedure was used in selecting 210 oil palm processors in the study area. Data were analyzed using percentages, frequencies, Occupational Hazard Indices and Stochastic Frontier Production Analysis (SFPA). Results revealed that 79%, 90.5% and 80.5% of the processors were male, married and educated respectively. Also, the mean age, processing experience and household size were 42 years, 15 years and 7 persons respectively. The most prevalent occupational hazards experienced were smoke irritation (100%), presser injury (94.3%) and spikelet injury (83.8%). The occupational hazards indices computed were, lost time rate, incidence rate and severity rate with values of 15.85, 23.77 and 2.4 respectively. SFPA revealed that the mean technical efficiency of the oil palm processors was 0.75. Furthermore, palm fruits (β = 0.662, p<0.01), the volume of water used (β = 0.180, p<0.05) and labor in man-day (β = 0.415, p<0.01) increased the production of palm oil. Also, processing experience (β = -0.110, p<0.05),), loss time rate (β = 0.087, p<0.05), incidence rate (β = 0.03, p<0.1), and severity rate (β = -0.098, p<0.01), decreased technical efficiency. The study concluded that occupational hazards had a negative influence on the technical efficiency of oil palm processors. The study recommended that stakeholders in oil palm processing should create health awareness and consistently research occupational hazards peculiar to oil palm processing as well as safety practices to enhance technical efficiency.